Dinamika Bahasa Visual dan Digital pada Generasi Alpha dalam Komunikasi Sehari-hari di Media Sosial - Iswatiningsih, Daroe; Inka Krisma Melati; Mohammad Khikam Zahidi (Paramasastra : Jurnal Ilmiah Bahasa Sastra dan Pembelajarannya, 2024)
Language represents its speakers, such is the case of language use in Generation Alpha in daily communication on social media. This study aims to describe the forms of visual and digital language in the Alpha generation and the meaning of visual and digital language in the Alpha generation. This type of research is qualitative, with a sociolinguistic approach. The data are in the form of linguistic units produced by the Alpha generation on social media in the form of visual and digital language. Data sources were obtained from social media platforms WhatsApp, Twitter, Instagram, and TikTok. The data were collected by documentation and capture screenshots of the four applications on social media. Data analysis using description analysis based on data findings, identification, categorization based on data form and meaning and then interpreting and presenting data. Based on the research results, (1) the form of visual language in Generation Alpha is expressed by the use of emojis, GIF memes, and stickers; while the use of digital language by Generation Alpha is expressed in the form of abbreviations, words or phrases, acronyms, shortening, reversed words, and written expressions. (2) The meaning of visual and digital language in Generation Alpha as (a) expression of emotion, (b) communication efficiency, (c) social and cultural identity; (d) nonverbal social interaction, and (e) communication creativity. The contribution of this research is expected to enrich creative and efficient communication, especially in communicating on social media in accordance with the context of use.